O estado e as políticas educacionais do governo Aécio Neves (2003- 2010) : uma análise a partir da reforma do Ensino Médio mineiro - Bragança Júnior, Anízio (2011)
This dissertation developed in the course of MS, Policy and management education line, Graduate Program in Education at the Federal University of Uberlandia, seeks to describe and to analyze the state and educational policies developed during the two terms of Aecio Neves government. Analyzing in a special way the high school, the research seeks to understand the assumptions of the reform implemented: Used State models, the objectives and functions of school and education, the purposes of management and its instruments. Based on a reading literature, creating prospects for debate at national and state government. It makes an analysis of official documents and describes the empirical reality of schools, from descriptions of research and experience of the author as a school teacher. The search develops as a final mechanism qualitative research which hears the workers involved in the ongoing reform, from visits to three schools in the state in Uberaba (MG). Analysis focuses on curriculum reform as a process full of different views inside school. It is described in the text of the situation and conditions of the state as a laboratory of experiences and the neoliberal programs, seeking to adapt education to reality mining is underway in several countries and school systems. Emphasizes the perspective the reform as a perspective to fill the curriculum guidelines established in high school in Brazil and its objectives. Analyzed subjectively, among the professionals, approaches and disputes that are formed around the projects implemented, and its immediate consequences in some schools surveyed, showing the different perspectives on the experiences of those involved.